Comparación electromiográfica de músculos suprahioideos, masetero y orbicular de los labios en niños y niñas de 1 a 5 meses de edad, alimentados con lactancia materna o biberón - Espinal, Gabriel; Hoyos, Luz María; Ramos, Clara; Salcedo, Bibiana; Arango, Adriana; Aguirre, Beatriz; Pérez, Luis Javier (Revista Facultad de Odontología Universidad de Antioquia, 2009)
A non probabilistic sample 0120 children between 1and 5months 01 age was selected, 10 children were breast led and 10 bottle led to which electromyography with surlace electrodes was performed on the supra hyoid muscles, masseter and orbicularis oris. For each muscle, 20 action potentials were selected, which meant a total 01200 action potentials per muscJe in each group. /t was lound that the highest muscJe activity in both groups was in the supra hyoids, lollowed by the orbicularis oris and the last the masseter. There were statical/y signiticent dilferences between the activity 01 the supra hyoids and orbicularis oris, but not with the masseter. The highest activity 01 the supra hyoid muscJes was lound in the breast led group, and the highest ectivity 01 the orbicu/aris oris was in the bottle led group.